(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
With the Internet of Things (IoT), you’ll be able to connect almost anything to the rest of the internet. It includes a wide range of hardware and software stacks as well as other technologies. An IoT ecosystem relies on data, people, devices, and communication. Because of India’s low level of technology penetration, an effective architecture for IoT must be built on current technological breakthroughs, capabilities that give an inexpensive and long-term solution, as well as entrepreneurial and social value. This is especially important for India. For every nation’s future growth, it’s critical to have a smart city. In order for the Indian government to provide a wide range of services to its people, IoT plays a critical role. Many heterogeneous and homogeneous systems may connect openly and effortlessly while having selective access to data for the construction of different digital services will be conceivable. The Internet of Things (IoT) is a technology aimed at facilitating the creative economy. In order to create smart cities, the federal government and several municipal governments are ready to make investments in the IoT sector.